Environmental Health issues: an imperative need for scientific literacy. - Athanasiou, Kyriacos (Eurasian Journal of Science andEnvironmental EducationVolume 10, Issue 2, 51 - 61, 2021)
The aim of this paper is to highlight issues of scientific literacy that characterize the Greek society in environmental and health issues, and the need to integrate the Teaching of Science and Biology with Health and Environmental Education. This is accomplished by the means of presentation of previous examples from the literature and through the presentation of studies of my own, as well. Thus, it is indicated that this and of course, other societies are characterized by a significant deficit in the familiarity with these matters. Next, I make a historical and personal appraisal on the evolution of the field of environmental health and genetics and try to make some review on its history, due to having the privilege of experiencing close correlation with it almost on its birth. Lastly, it is presented, a proposal for a university course adapted to the needs of present and future teachers combined to its evaluation. The latter was made through a questionnaire and the response of 153 students of education that highly rated the course as it was shown on the Likert scale. All this reveals emphatically the need for integrating the field of Environmental Health Education to Science and Biology teaching. Keywords: course, environmental health, health education, scientific literacy